Whitening Efficiency of Papain and Bromelain Gels in Removing Dental Stains - Stanca Cuc; Codruta Sarosi; Ioan Petean; Amalia Moldovan; Cecilia Bacali; Sorin Claudiu Man (Gels)
This study aimed to evaluate the micro-nanostructure and color changes of dental enamel after treatment with new gel formulations containing papain or bromelain. Eighty caries-free, extracted human teeth were randomly divided into two groups (n = 40) and stained by immersion in either coffee or Tedi juice for 4 h daily over five consecutive days. After staining, the samples were washed and stored in artificial saliva at 37 °C. The stained samples were then treated with four different whitening gels (GC, G1, G2, and Opalescence 15%) for 4 h daily. Following each treatment, the samples were rinsed and stored in artificial saliva. Color changes were measured using a digital spectrophotometer to assess CIEL*a*b* ΔE* and the Whiteness index (WI). The enamel micro-nanostructure was analyzed using SEM and AFM. Data were statistically analyzed using one-way ANOVA followed by Tukey’s HSD test. The results showed that gels containing papain and bromelain were more effective than the commercial gel in removing stains. SEM and AFM analysis indicated that papain was particularly effective for removing coffee stains, while bromelain was better for stains from natural juices. Healthy enamel has a Ra value of approximately 10 nm, which increases to about 40 nm after staining. Papain restored enamel roughness to approximately 8 nm for coffee stains and bromelain restored it to 11 nm for juice stains, delivering optimal results, while commercial gel ensures a roughness of about 15 nm after stain removal. CIELAB reveals notable changes in ΔE and WI after bleaching, revealing that papain gel is optimal for coffee stain removal and bromelain gel is optimal for natural juice stains. In conclusion, dental stains should be assessed by a dentist to determine the most suitable gel for achieving optimal results.